Situating the KTA gap in clinical research: Foregrounding a discontinuity in practices - Di Rienzo, Giulia (Frontiers in Psychology, 2023)
In this article, I will claim that we need to rearticulate the so-called "knowledge-to-action" gap metaphor in clinical research as a discontinuity of practices. In clinical research, there is a significant delay between the production of research results and their application in policy and practice. These difficulties are normally conceptualized through the metaphor of the "knowledge-to-action" gap between scientific knowledge and practical applications. I will advise that it is important to reformulate the terms of the problem, as they suggest the difficulty lies only in the results generated on one side (the laboratory), not reaching the other side (the clinic), and that crossing the gap requires us to simply optimize the transfer and exchange of knowledge. This perspective considers knowledge separate from the practices from which it was generated, making it into a thing that can be transported and transferred largely independently from the communities that produce or ‘possess’ it. The paper then revises the terms of the problem, shifting the focus from knowledge understood as independent from practical circumstances to the situated practices of knowing. Knowledge will then be understood as enacted in practice, emerging as people interact recurrently in the context of established practices. When people coming from different domains and with different “ends-in-view” must coordinate, they have to deal with conceptual and practical tensions, different ways of doing things with their surroundings, and different normative practices. Considering that, the KTA gap will be revised not as a gap between scientific results and their application in clinical practice, but as a discontinuity in how communities engage with their local contexts and what they perceive as relevant for their activities.